Comparison of removal techniques in the management of buried bumper syndrome: a retrospective cohort study of 82 patients - Daniela Mueller-Gerbes; Bettina Hartmann; Julio Pereira Lima; Michele de Lemos Bonotto; Christoph Merbach; Arno Dormann; Ralf Jakobs (Endoscopy International Open, 2017)
Background and study aims Buried bumper syndrome is an infrequent complication of percutaneous endoscopic gastrostomy (PEG) that can result in tube dysfunction, gastric perforation, bleeding, peritonitis or death. The aim of this study was to compare the efficacy of different PEG tube removal methods in the management of buried bumper syndrome in a large retrospective cohort. Patients and methods From 2002 to 2013, 82 cases of buried bumper syndrome were identified from the databases of two endoscopy referral centers. We evaluated the interval between gastrostomy tube placement and diagnosis of buried bumper syndrome, type of treatment, success rate and complications. Four methods were analyzed: bougie, grasp, needle-knife and minimally invasive push method using a papillotome, which were selected based on the depth of the buried bumper. Results The buried bumper was cut free with a wire-guided papillotome in 35 patients (42.7 %) and with a needle-knife in 22 patients (26.8 %). It could be pushed into the stomach with a dilator without cutting in 10 patients (12.2 %), and was pulled into the stomach with a grasper in 12 patients (14.6 %). No adverse events (AEs) were registered in 70 cases (85.4 %). Bleeding occurred in 7 patients (31.8 %) after cutting with a needle-knife papillotome and in 1 patient (8.3 %) after grasping. No bleeding was recorded after using a standard papillotome or a bougie (P < 0.05). Ten of 22 patients (45.5 %) treated with the needle-knife had a serious AE and 1 patient died (4.5 %). Conclusions We recommend that incomplete buried bumpers be removed with a bougie. In cases of complete buried bumper syndrome, the bumper should be cut with a wire-guided papillotome and pushed into the stomach.